Association Between Air Pollution and Emergency Consultations for Respiratory Diseases [Material Particulado y Gases Contaminantes en la Comuna de el Bosque ¿Cuánto Influyen en la Cantidad de Consultas por Enfermedades Respiratorias?] - Henriquez-Diaz, G (Sociedad Medica de Santiago, 2017)
Background: Air pollution has a direct influence on health. Aim: To determine the association between particulate matter and contaminant gas concentrations in the environment with the number of consultations for respiratory diseases in emergency rooms in Metropolitan Santiago, Chile. Material and Methods: During five years, the daily number emergency consultations for respiratory diseases and the daily concentrations of particulate matter and contaminant gases in a community of Santiago, were recorded. The degree of change of these variables during summer and winter was determined. Their correlation coefficients with a 0 to 100 days gap, were calculated. Results: During winter, there was a higher number of consultations and higher pollution levels, except for O3, which increased in summer. There were positive correlations between the concentrations of different pollutants (mainly 2.5 and 10 μm particulate matter, CO and NO2). There was a negative association between consultations for respiratory diseases and O3 concentrations, an almost negligible association with SO2 and variable positive and significant associations with the concentration of other pollutants, with variations according to the time gap. Conclusions: Pollution and respiratory diseases increase during winter. There are variable associations between pollutant concentrations and the number of consultations for respiratory diseases. © 2018, Sociedad Medica de Santiago. All rights reserved.